Kualitas Pelayanan Administrasi Kependudukan Kelurahan Sumurwelut, Surabaya Berbasis Teknologi - Lely Agustin; M. Kendry Widiyanto (Politeknik Kampar, 2024)
The quality of population administration services is one of the important roles in the population administration management process. Population administration service officers must provide excellent service to the community in order to provide welfare and ease the process of managing population administration. The purpose of this study is to see the extent of the quality of population administration services carried out by population administration service officers of the Kelurahan Sumurwelut office and also to see public satisfaction with the quality of population administration services based on Klampid New Generation (KNG) application technology carried out by Kelurahan Sumurwelut. The method used in this study is qualitative descriptive by obtaining data sources from interviews, observations, and documentation. The results of this study show that the quality of technology-based population administration services using the Klampid New Generation application carried out by Kelurahan Sumurwelut is very good. However, there are several factors that make the quality of population administration services hampered, namely when the occurrence of Klampid New Generation application servers that are error, unstable internet networks, and also people who do not understand the file requirements, and cannot take the time to come directly to the Kelurahan office to manage their files. This is not an obstacle to the decline in the quality of population administration services and public satisfaction with technology-based population administration services carried out by the Kelurahan Sumurwelut office.